The Minimum Dietary Diversity for Women of Reproductive Age (MDD-W) Indicator Is Related to Household Food Insecurity and Farm Production Diversity: Evidence from Rural Mali. Issue 3 (16th January 2019) - Adubra, Laura; Savy, Mathilde; Fortin, Sonia; Kameli, Yves; Kodjo, Niamké Ezoua; Fainke, Kamayera; Mahamadou, Tanimoune; Le Port, Agnes; Martin-Prevel, Yves
ABSTRACT: Background: The popularity of nutrition-sensitive interventions calls for high-quality monitoring and evaluation tools. In this context, the Minimum Dietary Diversity for Women of Reproductive Age (MDD-W), validated as a proxy of micronutrient adequacy, does fill a gap. However, because it is a newly endorsed indicator, information on its linkages with other dimensions of food and nutrition security is still scarce. Objective: The objective of this study was to investigate whether the MDD-W is related to household food insecurity and farm production diversity. Methods: A cross-sectional survey on a representative sample of 5046 women of reproductive age was conducted in the region of Kayes, Mali, in 2013. Dietary diversity was assessed through qualitative 24-h recall, and MDD-W was computed. MDD-W equaled 1 if the women consumed at least 5 different food groups and 0 otherwise. Food insecurity was measured using the Household Food Insecurity Access Scale and the Household Hunger Scale (HHS), and a farm production diversity score (FPDS) was calculated based on a count of food crops/livestock groups produced. Logistic regressions were used to assess the relation between MDD-W and the indicators of household food security. Results: Only 27% of women reached the MDD-W. These women consumed animal source foods and/or vitamin A-rich vegetables and fruits more frequently than did other women. Women from extremely food insecure households (moderate to severe hunger according to the HHS) were less likely to reach the MDD-W (OR: 0.70; 95% CI: 0.50, 0.97). One more group in the FPDS increased the odds of attaining the MDD-W (OR: 1.12; 95% CI: 1.06, 1.18). Conclusion: In the rural region of Kayes, Mali, women's dietary diversity, as measured by the MDD-W, was associated with household-level food security indicators. This study was registered at ISRCTN.org as ISRCTN08435964.